Living on the edge of African dreams: new identities for African and African diaspora Caribbean students in Brazil / Vivendo na fronteira de sonhos africanos: novas identidades para estudantes africanos e caribenhos da diáspora afro-caribenha no Brasil (Revista de Estudos da Linguagem, 2020)
Abstract: This article presents the results of a survey among African and Afro-Caribbean diaspora students in Brazil. They are participants of the federal PEC-G program, which grants tuition-free undergraduate spots in Brazilian universities. Before starting their undergraduate programs, however, they come to UFBA for linguistic and cultural instruction for a period of 8 months. The survey and the discussion of the results encompass interviews with 25 students about their cultural experiences and their intercultural development over the initial period of 6 months. They present a complex interaction of an originally middle-class background with professional aspirations in their home countries to a lower social status in a country with a history of slavery and racism. Many stories illustrate the conflicts they experience and the coping mechanisms they develop to navigate a new environment in which they will be immersed for a long period (at least 4 more years) while retaining as much of their original affiliations and identity as possible, especially considering that they are expected to return to their home countries after graduation.Keywords: Portuguese as a second language, identity and language acquisition, immersion and language learning, racism in Brazil.Resumo: Este artigo apresenta os resultados de uma pesquisa com estudantes africanos e da diáspora afro-caribenha no Brasil. São participantes do PEC-G, um programa do governo federal que oferece vagas em cursos de graduação gratuitamente em universidades brasileiras. Antes de começar a graduação, no entanto, eles vêm à UFBA para um curso de língua portuguesa e cultura por um período de 8 meses. A pesquisa e os resultados apresentados cobrem entrevistas com 25 estudantes sobre as suas experiências culturais e o seu desenvolvimento intercultural nos seus primeiros 6 meses. Aqui se revelam interações complexas entre sua situação social de classe média com ambições de ascensão social trazida dos países de origem em contraste com um status social diminuído em um país com uma história de escravidão e racismo. Muitos relatos ilustram os conflitos vivenciados e os mecanismos desenvolvidos para navegar um ambiente novo em que eles estarão por um longo período (no mínimo mais 4 anos) ao mesmo tempo em que conservam o máximo possível de suas afiliações e identidades, particularmente considerando que o programa prevê o seu retorno ao final da graduação.Palavras-chave: português como segunda língua, identidade e aquisição linguística, imersão linguística, racismo no Brasil.